Regulation of the Biosynthesis of Amino Acids of the Aspartate Family in Coliform Bacteria and Pseudomonads - Cohen, G. N. (1969)
The control of aspartokinase and homoserine dehydrogenase activities was compared in aerobic and fermentative pseudomonads (genera Pseudomonas and Aeromonas), and in coliform bacteria representative of the principal genera of the Enterobacteriaceae. Isofunctional aspartokinases subject to independent end-product control occur in the Enterobacteriaceae and in Aeromonas. In Pseudomonas, there appears to be a single aspartokinase, subject to concerted feedback inhibition by lysine and threonine. Within this genus, the sensitivity of aspartokinase to the single allosteric inhibitors varies considerably: the aspartokinase of the acidovorans group is little affected by the single inhibitors, whereas that of the fluorescent group is severely inhibited by either amino acid at high concentration. In all bacteria examined, homoserine dehydrogenase activity is inhibited by threonine; inhibition is more severe in aerobic pseudomonads than in the other groups. In most of the bacteria examined, either nicotinamide adenine dinucleotide (NAD) or nicotinamide adenine dinucleotide phosphate can serve as a cofactor for this enzyme, though the relative activity with the two pyridine nucleotides varies widely. Aerobic pseudomonads of the acidovorans group contain a homoserine dehydrogenase that is absolutely specific for NAD. The taxonomic implications of these findings are discussed.